Transition toward net zero emissions - Integration and optimization of renewable energy sources: Solar, hydro, and biomass with the local grid station in central Italy. (May 2023) - Gul, Eid; Baldinelli, Giorgio; Bartocci, Pietro; Shamim, Tariq; Domenighini, Piergiovanni; Cotana, Franco; Wang, Jinwen; Fantozzi, Francesco; Bianchi, Francesco
Abstract: Clean energy technologies are playing a vital role in energy transition, realization of Net-Zero emission goals, and satisfying increasing energy demands. The objective of this work is to investigate the potentials of renewable energy sources and propose a state-of-the-art new grid connected energy system model, which increases the penetration of renewable energies in the medium-size Municipality of Perugia, Central Italy. The presented energy system model integrates and optimises renewable energy sources mainly consisting of hydro, solar, and biomass, by implementing new dispatch strategies and advanced mathematical model. The developed model maximises the power generation of each source based on the least Net Present Cost and the lowest Levelized Cost of Energy and balances the fluctuating load demand by using combined dispatch strategies. Furthermore, demand-side load management strategies are implemented for efficient energy management. An economic and environmental analysis has been performed to evaluate the impact of the proposed system. The results show that a significant amount of clean energy (33.2 GWh/year) is produced at the lowest Levelized Cost of Energy of 0.067 €/kWh. Moreover, up to 78% of the energy demand of the selected community is covered by renewable energies, which evades 13, 452 tons of CO2 emission yearly.